2019
DOI: 10.1007/s11136-019-02152-6
|View full text |Cite
|
Sign up to set email alerts
|

The humanistic burden of advanced non-small cell lung cancer (NSCLC) in Europe: a real-world survey linking patient clinical factors to patient and caregiver burden

Abstract: Purpose Advanced non-small cell lung cancer (aNSCLC) impacts the lives of patients and their caregivers. This analysis examined the association between patient clinical characteristics and patient and caregiver humanistic burden. Methods Data for patients with aNSCLC and their informal caregivers in France, Germany and Italy, were collected between May 2015 and June 2016 via chart review and patient and caregiver surveys. Patients and caregivers completed validated inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…The remaining 24 studies were excluded from subsequent analyses [ 59 82 ]. Among the excluded studies, four did not measure HRQoL in patients [ 72 , 77 , 81 , 82 ], nine did not use valuation by members of the general public [ 59 , 60 , 63 , 69 , 71 , 72 , 74 , 81 , 82 ], 11 did not use a choice-based method for valuation [ 59 , 63 , 65 , 67 – 71 , 74 , 76 , 81 ], and nine had missing data on one or more of these items [ 61 , 62 , 64 , 66 , 73 , 75 , 78 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 24 studies were excluded from subsequent analyses [ 59 82 ]. Among the excluded studies, four did not measure HRQoL in patients [ 72 , 77 , 81 , 82 ], nine did not use valuation by members of the general public [ 59 , 60 , 63 , 69 , 71 , 72 , 74 , 81 , 82 ], 11 did not use a choice-based method for valuation [ 59 , 63 , 65 , 67 – 71 , 74 , 76 , 81 ], and nine had missing data on one or more of these items [ 61 , 62 , 64 , 66 , 73 , 75 , 78 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our study found that patients in MDEs had an average utility value of 0.41, and this value was higher for patients in improved health states. In two real-world studies, a utility value was estimated at 0.80 in 505 French patients with untreated chronic hepatitis C and at 0.67 in 1030 European patients with advanced non-small cell lung cancer [ 39 , 40 ]. Ara et al [ 41 ] found that the average utility value for patients with mental illness, depression, or neurosis was 0.61.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, only four studies measured QoL in Italian lung cancer patients through the administration of the EORTC QLQ-C30. Two of them were international studies and involved several countries, with all of them focusing on non-small cell lung cancer (Di Maio et al, 2004; Maione et al, 2005; Koller et al, 2017; Wood et al, 2019).…”
Section: Introductionmentioning
confidence: 99%